Management of Hepatitis C in Dialysis Dependent Patients. - Khalid, Fawad; Ansar, Muhammad Omair (Pakistan Journal of Kidney Diseases, 2021)
Prevalence of Hepatitis C (HCV) is quite high in Pakistan and in particular among maintenance hemodialysis (MHD) patients. HCV is associated with increasing morbidity and mortality among MHD patients. The current availability of direct acting antiviral therapy has changed the canvas for HCV prevalence in many countries. Aim of our study was to evaluate the status of HCV prevalence and its management at our center. Methods: This descriptive study was conducted at Nawaz Sharif Kidney Hospital Swat, Pakistan to evaluate the seroprevalence of HCV among MHD patients. Data regarding HCV status, PCR positivity and number of patietns on active treatment were evaluated. Results: A total of 109 patients were undergoing MHD in this study. The prevalence of patient who had HCV was 40 (36.6%). All patietns had PCR done and out of them PCR was positive in 28 Patients. All except 4 of the 28 patients had been started on HCV treatment with direct antiviral therapy for HCV. Conclusion: almost all of HCV PCR positive patients were being treated with DAA in our dialysis unit.